2002
DOI: 10.1002/gcc.10030
|View full text |Cite
|
Sign up to set email alerts
|

Combined restriction landmark genomic scanning and virtual genome scans identify a novel human homeobox gene, ALX3, that is hypermethylated in neuroblastoma

Abstract: Restriction landmark genome scanning (RLGS) allows comparative analysis of several thousand DNA fragments in the genome and provides a means to identify CpG islands that are altered in tumor cells as a result of amplification, deletion, or methylation changes. We have developed a novel informatics tool, designated virtual genome scan (VGS), that makes it possible to predict automatically the sequence of fragments in RLGS patterns by matching to the human genome sequence. A combination of RLGS and VGS was utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…The sequence of the rat Alx3 homeodomain is identical to that of the Alx3 homeodomain from human (27), hamster (7), and mouse (8). Outside the homeodomain, rat Alx3 exhibits a high degree of amino acid identity with the known Alx3 orthologs from other species (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The sequence of the rat Alx3 homeodomain is identical to that of the Alx3 homeodomain from human (27), hamster (7), and mouse (8). Outside the homeodomain, rat Alx3 exhibits a high degree of amino acid identity with the known Alx3 orthologs from other species (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Isolation of Rat Alx3 cDNA-A degenerate reverse transcriptase-PCR-based screen initially aimed at identifying orthodenticle-related homeodomain genes expressed in neural cell lines yielded several homeodomain region-encoding clones whose translated sequence was identical to that of mouse, human, and hamster Alx3 (7,8,27). Clones encoding the homeodomains of Otx1 and Otx2 were also identified, but no additional Otx-related genes were detected.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25] Restriction landmark genome scanning (RLGS) has been widely used for comparison of genomic DNA copy number, 11,26 -31 and to detect changes in DNA methylation among related tissues of interest. [32][33][34][35] For RLGS, genomic DNA is cleaved with a rare-cutting restriction endonuclease and the cleavage sites are radioactively labeled before first-dimension electrophoresis. The separated DNA fragments are then digested in situ with a frequent-cutting restriction endonuclease before seconddimension electrophoresis.…”
mentioning
confidence: 99%
“…Genome-wide analysis comparing T01 with T02 and T03 identified 118 probes clustered in 105 regions that exhibited significantly different methylation (Supplemental Table 2). Upon further examination, no methylation alterations affected genes previously reported to be mutated in sporadic PA tumors (Wimmer et al 2002b;Tada et al 2003;Sharma et al 2005;Deshmukh et al 2008;Jones et al 2008;Pfister et al 2008). For most of the 42 probes localized within the NF1 gene region, we found that methylation patterns were similar in all five PA tumor samples analyzed.…”
Section: Resultsmentioning
confidence: 48%